Effect of Shangke Zhitong Ointment Kinesio Tape on Ankle Sprain - WANG Qiang; LIU Zhiyang; JU Shaohua; LI Xiaodong; HUANG Jichao; XIANG Ning (康复学报)
ObjectiveTo observe the effect of Shangke Zhitong ointment kinesio tape on ankle sprain.MethodsA total of 123 patients with ankle sprain in the Hospital of Physical Education Affiliated to Chengdu Institute of Physical Education from January to October 2021 were randomly divided into control group, combined group and Shangke kinesio tape group, with 41 cases in each group. All groups were treated following the basic principles of PRICE for acute injury. In addition, the control group received kinesio tape therapy; the combined group received kinesio tape and Shangke Zhitong ointment; the Shangke kinesio tape group received Shangke Zhitong ointment kinesio tape. The three groups changed the application once a day, five times a week, lasting for two weeks. Before treatment and after two weeks of treatment, visual analogue score (VAS), swelling degree measurement, American orthopedic foot and ankle society-ankle hindfood scale (AOFAS-AHS), traditional Chinese medicine (TCM) syndrome score (local tenderness, local swelling, local blood stasis, limited activity) were evaluated, and laboratory index test [interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), superoxide dismutase (SOD), malondialdehyde (MDA), fibroblast growth factor-2 (FGF-2), transforming growth factor-β1 (TGF-β1) , matrix metalloproteinase (MMP-9)] were performed and skin adverse reactions were observed.Results(1) VAS score, swelling degree of ankle joint and AOFAS-AHS score: compared with before treatment, VAS score and swelling degree in the three groups decreased significantly after treatment, while AOFAS-AHS score increased significantly after treatment (P<0.05). Compared with the control group, the VAS score and swelling degree were significantly lower in the combined treatment group and the Shangke kinesio tape group after treatment, and the AOFAS-AHS score was significantly higher (P<0.05). Compared with the combined group, the degree of swelling in the Shangke kinesio tape group after treatment was significantly lower, and the AOFAS-AHS score was significantly higher (P<0.05). (2) TCM syndrome score: compared with those before treatment, the scores of local tenderness, local swelling, local blood stasis and activity limitation in the three groups were significantly lower after treatment (P<0.05). Compared with the control group, the scores of local tenderness, local swelling, local blood stasis and activity limitation in the combined group and the Shangke kinesio tape group were significantly lower after treatment (P<0.05). Compared with the combined group, the scores of local swelling and activity limitation in the Shangke kinesio tape group were significantly lower after treatment (P<0.05). (3) Laboratory tests: compared with that before treatment, serum IL-1β, TNF-α, MDA, FGF-2, TGF-β1, MMP-9 in the three groups decreased significantly, and the level of SOD increased significantly after treatment (P<0.05). Compared with the control group, serum IL-1β, TNF-α, MDA, FGF-2 and MMP-9 in the combined group were significantly lower after treatment (P<0.05); serum IL-1β, TNF-α, MDA, FGF-2, TGF-β1, MMP-9 in the Shangke kinesio tape group were significantly lower after treatment, SOD was significantly higher (P<0.05). Compared with the combined group, IL-1β, MDA, FGF-2, TGF-β1, MMP-9 in the Shangke kinesio tape group after treatment were significantly lower, SOD was significantly higher (P<0.05).ConclusionShangke Zhitong ointment kinesio tape can inhibit inflammation, oxidative stress and other reactions after ankle sprain, relieve local swelling, pain, movement limitation and other symptoms of ankle joint, and effectively improve the ankle function of patients, which is recommended for clinical application.